Social Media as a Support for Business Communication in the Digital Era - Dwi Agustin; Saprida Saprida; Fadilla Fadilla; Havis Aravik; Ahmad Tohir (Penerbit dan Percetakan CV.Picmotiv, 2026)
In this digital era, we understand that the development of information, communication, and digital technology has a big impact on business growth. Because of these technological advancements, businesses are increasingly using digital media as a communication tool. Besides helping businesses communicate with consumers and customers, social media is also used by business owners as a marketing tool to grow their businesses. This article is based on data collected from many online sources, including several journals, books, and websites. The purpose of this study is to find out whether social media can function as a communication tool for businesses in the digital era. This study uses a qualitative approach, where the research is conducted by comparing several journals and drawing conclusions to create a new article from previous research done by other researchers. The study also uses a systematic literature review (SLR) method, which collects data from previously validated research. The purpose of this article is to better understand how social media can play an important role in business communication in the digital era.